Analisis dan Desain Model UI/UX untuk Pengguna Manusia Lanjut Usia dalam Transformasi Bisnis Pertanian Digital - Herdin Yohnes Madawara; Irwan Sembiring; Budhi Kristianto (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2024)
Digital agriculture faces challenges, namely in integrating Elderly People (SENIORS) in digital transformation. The purpose of the study is to analyze and design UI/UX models according to user needs, expectations, and challenges. The method used is the Design Thinking approach which begins with literature study, then interviews are conducted to identify problems faced by users, and analyze the need to determine problem priorities. UI/UX prototypes are carried out to design solutions that suit user needs, and evaluations are carried out to collect user feedback. The data is assessed through the System Usability Scale (SUS) approach to appraise the designed user interface (UI). The evaluation results showed a